Application of Analysis and Risks Assessment Methods for Quality Activities Assurance at the University - Dolzhansky, A.M.; Proydak, Yu.S.; Revenko, O.O. (Science and Innovation, 2024)
On the example of the National Metallurgical Academy of Ukraine the authors have identified the risks in the university activities using the recommendations of ISO 9001:2015 and ISO 31000 series and applying the known methods for analysis of the essential aspects of organization functioning (PEST-analysis, SWOT-analysis, SNW-analysis). The assessment of significance of these risks using FMEA system enabled the authors to determine the appropriate immediate safety measures.